1998
DOI: 10.1128/jvi.72.10.7807-7814.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Secondary Structure of the R Region of a Murine Leukemia Virus Is Important for Stimulation of Long Terminal Repeat-Driven Gene Expression

Abstract: In addition to their role in reverse transcription, the R-region sequences of some retroviruses affect viral transcription. The first 28 nucleotides of the R region within the long terminal repeat (LTR) of the murine type C retrovirus SL3 were predicted to form a stem-loop structure. We tested whether this structure affected the transcriptional activity of the viral LTR. Mutations that altered either side of the stem and thus disrupted base pairing were generated. These decreased the level of expression of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Primer extension analysis indicated that the RSL affected the levels of cytoplasmic RNA. Nuclear run-on assays indicated that deletion of the RSL had a small effect on transcriptional initiation and no effect on RNA polymerase processivity (15,16). Thus, the main effect of the RSL was on one or more steps that occurred after the template was transcribed by RNA polymerase.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Primer extension analysis indicated that the RSL affected the levels of cytoplasmic RNA. Nuclear run-on assays indicated that deletion of the RSL had a small effect on transcriptional initiation and no effect on RNA polymerase processivity (15,16). Thus, the main effect of the RSL was on one or more steps that occurred after the template was transcribed by RNA polymerase.…”
mentioning
confidence: 99%
“…We previously showed that R region sequences of MuLV SL3 affected expression of a reporter gene under the control of a viral LTR (15,16). R region sequences from Moloney MuLV or feline leukemia virus could substitute for the SL3 element.…”
mentioning
confidence: 99%
See 3 more Smart Citations